2022
DOI: 10.3390/molecules27103077
|View full text |Cite
|
Sign up to set email alerts
|

Structural Modeling of TRPA1 Ion Channel—Determination of the Binding Site for Antagonists

Abstract: TRPA1 is a transmembrane cation channel, one of the most promising targets in the context of respiratory diseases. Its general structure has already been experimentally resolved, but the binding site of TRPA1 antagonists such as HC-030031, a model methylxanthine derivative, remains unknown. The present study aimed to determine the potential binding site of xanthine antagonists and to describe their binding mode, using a molecular modeling approach. This study represents the first attempt to bring together site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…We observed a new putative binding site of phenylcoumarins located in TRPA1's ankyrin repeat domain. This ARD binding site has also been reported by Gawalska et al 17 ARD consists of a short, typically 33 amino acid long residue and it forms an antiparallel helix-turn-helix structure followed by a β-hairpin loop. 11 It has shown that ankyrin domain can have interactions with small molecules leading to the activation of the ion channel.…”
supporting
confidence: 75%
“…We observed a new putative binding site of phenylcoumarins located in TRPA1's ankyrin repeat domain. This ARD binding site has also been reported by Gawalska et al 17 ARD consists of a short, typically 33 amino acid long residue and it forms an antiparallel helix-turn-helix structure followed by a β-hairpin loop. 11 It has shown that ankyrin domain can have interactions with small molecules leading to the activation of the ion channel.…”
supporting
confidence: 75%
“…Allyl isothiocyanate [ 110 ], 15-deoxy-delta(12,14)-prostaglandin J(2) [ 77 ], and other electrophilic agonists activate TRPA1 by covalently modifying cysteine residues [ 111 ]. Three of these cysteine residues, C621, C641, and C665, are critical for the activation of electrophilic stimuli [ 112 ], which are all located in the region containing the ankyrin repeats, linker, and pre-S1-helix [ 11 ]. It has been found that C621 is located in the first helix-turn-helix, C641 is in the first strand of the putative β-sheet, and C665 is in the flexible loop connecting the β-strands to the second helix-turn-helix, further clarifying the spatial distribution of cysteine residues [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…TRPA1 is mainly involved in the expression of primary sensory neurons and the dorsal root ganglion (DRG) [ 10 ]. As such, TRPA1 has promising research potential in pain-related and respiratory diseases [ 11 ] and is currently being investigated as a therapeutic target because of its anti-oxidant, anti-apoptotic, and anti-inflammatory mechanisms. Emerging disciplines such as chemical optogenetics [ 12 ] and sequence analysis [ 13 ] are now being carried out, further enriching the research field of TRPA1.…”
Section: Introductionmentioning
confidence: 99%
“…The structural model of the TRPA1 ion channel was previously described, and was characterized in retrospective virtual screening by the following parameters: EF 1 % reached 33, BEDROC 0.785 (α = 20) and AUAC 0.96 [32]. On its basis, a grid file for docking containing hydrogen bond constraint on Asn-855 (a hydrogen bond donor) was prepared.…”
Section: Molecular Modelingmentioning
confidence: 99%
“…ZINC306137810, in the TRPA1 binding pocket, showed hydrogen bonding with Asn-855 as well as a π-π stacking interaction with Trp-711. Both of these amino acids are essential for the inhibitory activity of reference compound HC-030031 [32,38], therefore the potential activity of ZINC306137810 on this ion channel can be assumed. Additionally, the position of the selected MTDL is stabilized by hydrogen bonds with Glu-854 and Arg-1011.…”
Section: Virtual Screeningmentioning
confidence: 99%